The Reemergence of the Afghan Taliban in Afghanistan and Its Impact on Militant Groups in Pakistan (A Case Study of the TTP) - Jan, Attaullah (Journal of Peace, Development and Communication, 2023)
This research work attempts to investigate the militant groups’ activities against Pakistan after the re-emergence of the Afghan Taliban in Afghanistan. The core objective of this research is to highlight the security threats that have emerged as challenges to Pakistan, especially in Khyber Pakhtunkhwa province. Pakistan perceived that the Taliban coming into power would reduce terrorist threats to Pakistan. However, after the Taliban took power, Pakistan faced a new wave of militancy, with the TTP in particular becoming a major security concern. The research findings disclosed that the Taliban interim government in Afghanistan encouraged militant groups like the TTP, BLA and IS-K based in Afghanistan to engage in disruptive activities against Pakistan. A qualitative research approach was applied to this study, in which the primary data was collected through personal interviews and the secondary data was collected through published sources. A non-probability judgmental sampling technique through a semi-structured interview was conducted. Moreover, the study recommends that the threat to peace in Afghanistan persists and will have repercussions for Pakistan's stability in the future. However, if the Afghan Taliban interim government addresses the legitimate concerns of their neighbouring states, it can bring peace and stability to the region.